The impact of atmospheric oxidation on hygroscopicity and cloud droplet activation of inorganic sea spray aerosol - Bernadette Rosati; Sigurd Christiansen; Anders Dinesen; Pontus Roldin; Andreas Massling; E. Douglas Nilsson; Merete Bilde (Scientific Reports, 2021)
Abstract Sea spray aerosol (SSA) contributes significantly to natural aerosol particle concentrations globally, in marine areas even dominantly. The potential changes of the omnipresent inorganic fraction of SSA due to atmospheric ageing is largely unexplored. In the atmosphere, SSA may exist as aqueous phase solution droplets or as dried solid or amorphous particles. We demonstrate that ageing of liquid NaCl and artificial sea salt aerosol by exposure to ozone and UV light leads to a substantial decrease in hygroscopicity and cloud activation potential of the dried particles of the same size. The results point towards surface reactions on the liquid aerosols that are more crucial for small particles and the formation of salt structures with water bound within the dried aerosols, termed hydrates. Our findings suggest an increased formation of hydrate forming salts during ageing and the presence of hydrates in dried SSA. Field observations indicate a reduced hygroscopic growth factor of sub-micrometre SSA in the marine atmosphere compared to fresh laboratory generated NaCl or sea salt of the same dry size, which is typically attributed to organic matter or sulphates. Aged inorganic sea salt offers an additional explanation for such a measured reduced hygroscopic growth factor and cloud activation potential.